Bridging Clinical Practice and Technology: A Collaborative Approach between Nursing and Health Informatics - Huda Abdullah Hamammi; Eman Abdullah Hamami; Zahra Husien Ali Al Therwy; Magad Mohammad Seed Alblawi; Bayan Khalid Alshuwaikhat; Azzah Abdulla Mohssin Alshahrani; Sarah Abdullah Aldosari; Ali Hussain Mashyakhi; Msawa Mohsen Hakami; Mohammed Hadi Mohasen Khourmi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
This paper discusses the key linking or bridging role of nursing informatics between clinical practice and technology in the improvement of patient care, enhancement of workflow efficiency, and ensuring patient safety. Health informatics combines data, information, and knowledge that support clinical decisions, thus facilitating the work of the nurse in managing patient data and reducing the occurrence of errors. It has eased the delivery of clinical care services due to the use of EHRs and data-driven platforms in the clinical workflow, culminating in evidence-based practices. The paper also focuses on developing nursing informatics competencies and collaborative works between nursing professionals and health informatics experts for better optimization of the use of the digital tool within a clinical setting. It means that nursing informatics really has the power to enable a revolution in health care toward better patient outcomes through education, collaboration, and positive attitudes toward technology